Inflaming sex differences in mood disorders. (January 2019) - Rainville, Jennifer; Hodes, Georgia
Abstract Men and women often experience different symptoms or rates of occurrence for a variety of mood disorders. Many of the symptoms of mood disorders overlap with autoimmune disorders, which also have a higher prevalence in women. There is a growing interest in exploring the immune system to provide biomarkers for diagnosis of mood disorders, along with new targets for developing treatments. This review examines known sex differences in the immune system and their relationship to mood disorders. We focus on immune alterations associated with unipolar depression, bipolar depression, and anxiety disorders. We describe work from both basic and clinical research examining potential immune mechanisms thought to contribute to stress susceptibility and associated mood disorders. We propose that sex and age are important, intertwined factors that need to be included in future experimental designs if we are going to harness the power of the immune system to develop a new wave of treatments for mood disorders.